B-doped iron monatomic catalyst as well as preparation method and application thereof
Through the preparation method of B-doped iron single atom catalyst, the problems of low degradation efficiency, poor stability and large acid and alkali consumption in the prior art are solved, and micropollutants and microplastics are efficiently degraded, and the degradation products can be resource-based and the preparation process is environmentally friendly.
Patent Information
- Application Number
- CN202411798621.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-14
AI Technical Summary
Existing carbon-based single-atom catalysts have low degradation efficiency and poor stability in the process of advanced oxidation degradation of micropollutants and microplastics, and require a large amount of acid to regulate, resulting in large acid and alkali consumption and environmental pollution.
Using a B-doped iron single atom catalyst, a supramolecular coordination complex is formed by hydrogen bond assembly of boric acid and urea, combined with hydrogen bond assembly of metal organic complexes, an iron single atom catalyst with synergistic effects is generated, and a catalyst with iron atom dispersion is obtained by pyrolysis.
The efficiency of Fenton-like degradation of sulfamethoxazole is significantly improved, the ability to activate PMS is enhanced, and the ability to achieve 100% sulfamethoxazole degradation within 5 minutes and completely mineralizes it to carbon dioxide and water. At the same time, it has good degradation ability for microplastics, and the degradation products can be re-resourced and do not require acid leaching, making them more sustainable and environmentally friendly.
Smart Images

Figure CN119608209A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of water treatment technology and environmental functional materials, and specifically relates to a B-doped iron single-atom catalyst and a preparation method and application thereof. Background Art
[0002] Micropollutants (MPs), such as pharmaceuticals, personal care products, and pesticides, are common types of micropollutants. Exposure concentrations of these micropollutants are higher than the natural background levels of chemical concentrations in water bodies (the natural background levels of chemical concentrations in water bodies range from ng / L to μg / L), posing a high risk to ecological safety and clean water supply. At the same time, about 380 million tons of plastic waste are generated worldwide each year. The improper disposal of these waste plastics has led to serious environmental crises, including land, water, and marine pollution, microplastic pollution, and harm to wildlife. Micropollutants and microplastics have potential impacts on human health through bioaccumulation.
[0003] In many catalytic reactions, the uniformity of active sites is a necessary prerequisite for high product selectivity. So far, various catalysts have been used for the advanced oxidation degradation of micropollutants and microplastics based on potassium permonosulfate (PMS), among which carbon-based materials and single atom catalysts (SACs) are the two most promising catalysts due to their tunable active sites and acceptable activation properties. Singlet oxygen ( 1 O2) is an excellent active oxygen with mild oxidizing ability, especially with other free radicals (such as OH, SO4 2- and O2 - )compared to, 1 O2 has great potential in wastewater treatment. However, current carbon-based single-atom catalysts do not all have good Fenton-like activity and corresponding 1 O2 selectivity, and in traditional advanced oxidation degradation, the catalyst needs to add a large amount of acid to adjust the wastewater containing micropollutants and microplastics, which consumes a lot of acid and alkali. For this reason, acid leaching of the catalyst is proposed, but there is still the problem of acid and alkali consumption, causing certain environmental pollution. Therefore, it is necessary to rationally design cutting-edge catalysts with clear, flexible and rich active sites to efficiently generate in the process of advanced oxidation degradation of micropollutants and microplastics by PMS. 1 O2, is crucial to solving problems such as low degradation efficiency, poor stability and environmental pollution, but is still lacking. Summary of the invention
[0004] In view of the deficiencies of the prior art, the object of the present invention is to provide a B-doped iron single-atom catalyst.
[0005] Another object of the present invention is to provide a method for preparing a B-doped iron single-atom catalyst, which takes B coordination sites as constituent units, assembles supramolecular coordination complexes (SCCs) based on hydrogen bonds of boric acid (B source) and urea, utilizes hydrogen bond assembly of SCCs and metal organic complexes (MOC) (Fe source) to produce iron single atoms having a synergistic effect of SCCs and MOC, and subsequently, obtains an iron single-atom catalyst with dispersed iron atoms by pyrolyzing the SCCs and MOC assemblies.
[0006] Another object of the present invention is to provide a B-doped iron single-atom catalyst for use in the degradation of microplastics or pollutants, wherein the iron single-atom catalyst can selectively produce 1 O2 can activate PMS to degrade pollutants, and the degradation effect is excellent.
[0007] The purpose of the present invention is achieved through the following technical solutions.
[0008] A method for preparing a B-doped iron single-atom catalyst comprises the following steps:
[0009] 1) Dispersing urea and B source uniformly in a first solvent to obtain a mixed solution, uniformly mixing an Fe source solution, a polyether F127 solution and the mixed solution, and freeze-drying to obtain a precursor, wherein the Fe source solution is a mixture of the Fe source and the second solvent, the polyether F127 solution is a mixture of the polyether F127 and the second solvent, and the ratio of urea to B in the B source and Fe in the Fe source is 50: (2.5-5.5): (0.02-0.08) in terms of the amount of the substance;
[0010] In the step 1), the ratio of the amount of Fe in the Fe source to the mass of the polyether F127 is (0.02-0.08):200, the unit of the amount of Fe is mmol, and the unit of the mass is mg.
[0011] In the step 1), the concentration of the Fe element in the Fe source solution is 3.5-4.5 mmol / L, and the concentration of the polyether F127 in the polyether F127 solution is 35-45 mg / mL.
[0012] In the step 1), the ratio of the amount of urea to the volume of the first solvent is 50:(9-11), the unit of the amount of urea is mmol, and the unit of the volume is mL.
[0013] In the step 1), the B source is boric acid, the Fe source is ferric chloride hexahydrate (FeCl3·6H2O), the first solvent is deionized water, and the second solvent is ethanol.
[0014] In the step 1), urea and B source are uniformly dispersed in the first solvent by ultrasound for 15 to 20 minutes.
[0015] 2) calcining the precursor at 780-820° C. for 1.8-2.2 h in a nitrogen or inert gas atmosphere to obtain a B-doped iron single atom catalyst.
[0016] In the step 2), the heating rate of the calcination is 4.5-5°C / min.
[0017] In the step 2), the precursor needs to be ground before calcination.
[0018] Application of the above-mentioned B-doped iron single-atom catalyst in the degradation of microplastics or pollutants.
[0019] In the above technical solution, the pollutant is sulfamethoxazole (SMX), and the microplastic is polyvinyl chloride (PVC) or polylactic acid (PLA).
[0020] In the above technical solution, the reaction of degrading microplastics or pollutants is a Fenton-like degradation that requires the addition of potassium permonosulfate complex salt (PMS).
[0021] In the above technical solution, the conditions for degrading microplastics are normal pressure, and the pH for degrading microplastics or pollutants is 6.0 to 8.0.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] (1) The B-doped iron single-atom catalyst of the present invention significantly improves the efficiency of Fenton-like degradation of sulfamethoxazole and enhances the ability to activate PMS, achieving 100% degradation of sulfamethoxazole within 5 minutes. After 10 minutes, sulfamethoxazole can be completely mineralized into carbon dioxide and water, providing an effective and feasible method for improving the degradation of micropollutants such as SMX.
[0024] (2) The B-doped iron single-atom catalyst of the present invention has good degradation ability for microplastics (polyvinyl chloride (PVC) and polylactic acid (PLA)). After degradation, the degradation products of microplastics have a wide range of uses and can be reused as resources, providing an effective and feasible method in the field of microplastic resource conversion.
[0025] (3) The degradation reaction of the B-doped iron single-atom catalyst of the present invention is a Fenton-like degradation, and the degradation process efficiently generates 1 O2, improving the degradation ability.
[0026] (4) The preparation method of the present invention does not require acid leaching, making the preparation and degradation process more sustainable and environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 X-ray diffraction (XRD) patterns of the carbon nanocatalysts prepared in Comparative Examples 1 to 3 and the B-doped iron single atom catalyst prepared in Example 1;
[0028] Figure 2 This is a transmission electron microscope (TEM) image of the B-doped iron single-atom catalyst prepared in Example 1;
[0029] Figure 3 Energy dispersive X-ray spectroscopy (EDS) mapping diagram of the B-doped iron single atom catalyst prepared in Example 1, (a) is the C element, (b) is the N element, (c) is the B element, and (d) is the Fe element;
[0030] Figure 4 This is a Fourier transform extended X-ray absorption fine structure (FT-EXAFS) spectrum of the B-doped iron single atom catalyst prepared in Example 1;
[0031] Figure 5 The figures are the effects of different catalysts on the degradation of sulfamethoxazole, wherein (a) is a catalyst which is one of the B-doped iron single-atom catalysts prepared in Examples 1 to 8, and (b) is a catalyst which is one of the B-doped iron single-atom catalysts prepared in Example 1 and the carbon nanocatalysts prepared in Comparative Examples 1 to 3;
[0032] Figure 6 The electron paramagnetic resonance (EPR) spectra of PMS group, FeBCN group, FeCN+PMS group and FeBCN+PMS group, (a) ·OH and SO4 2- Electron paramagnetic resonance (EPR) spectrum, (b) is ·O 2- Electron paramagnetic resonance (EPR) spectrum, (c) 1 O2 electron paramagnetic resonance (EPR) spectrum;
[0033] Figure 7 O 2- and 1 O2 electron paramagnetic resonance (EPR) comparison spectra;
[0034] Figure 8 The degradation products and pathways of sulfamethoxazole degradation by the B-doped iron single-atom catalyst prepared in Example 1;
[0035] Fig. 9 Gas chromatography (GC) mass spectrum of the B-doped iron single-atom catalyst prepared in Example 1 for degradation of microplastics. DETAILED DESCRIPTION
[0036] The technical solution of the present invention is described in detail below in conjunction with specific embodiments.
[0037] In the following examples, the gas chromatography (GC) mass spectra were detected by an HP 6890-Plus gas chromatograph installed on a 5973 mass selective detector (Agilent, USA), and the detection conditions were set as follows: the capillary column was a fused silica capillary column (CP-SIL 8CB, column length × inner diameter: 30 cm × 0.25 mm), the carrier gas was helium, and before the sample was measured, the GC oven was kept at 80° C. for 10 minutes, the temperature was increased to 270° C. at a rate of 50° C. / min, and kept at 270° C. for 3 minutes to stabilize the GC oven, the transfer line temperature was 280° C., the MS ion source temperature was 230° C., and the electron impact ionization was maintained at 70 eV.
[0038] Examples 1 to 8
[0039] A method for preparing a B-doped iron single-atom catalyst comprises the following steps:
[0040] 1) Urea and B source (B source is boric acid) are added to the first solvent, ultrasonicated for 15 minutes to disperse them evenly to obtain a mixed solution, and the Fe source solution, polyether F127 solution (used as a polymerization agent) and the mixed solution are mixed evenly, and freeze-dried to obtain a precursor, wherein the Fe source solution is a mixture of the Fe source (the Fe source is ferric chloride hexahydrate) and the second solvent, and the concentration of the Fe element in the Fe source solution is 4mmol / L. The polyether F127 solution is a mixture of polyether F127 and the second solvent, and the concentration of polyether F127 in the polyether F127 solution is 40mg / mL. The first solvent is deionized water, and the second solvent is ethanol. According to the amount of substance, the ratio of B in urea, B source, and Fe in Fe source is W. The ratio of the amount of urea to the volume of the first solvent is 50:10, the unit of the amount of substance is mmol, and the unit of the volume is mL. The ratio of the amount of Fe in the Fe source to the mass of polyether F127 in the polyether F127 solution is Z, the unit of the amount of Fe is mmol, and the unit of the mass is mg.
[0041] 2) The precursor was ground in a quartz mortar, and after grinding, the temperature was raised to 800°C at a rate of 5°C / min in an argon gas atmosphere and calcined at 800°C for 2h to obtain a B-doped iron single atom catalyst.
[0042] The B-doped iron single-atom catalysts prepared in Examples 1 to 8 are shown in Table 1.
[0043] Table 1
[0044]
[0045]
[0046] Comparative Example 1
[0047] A method for preparing a carbon nanocatalyst (code: NC) comprises the following steps:
[0048] 1) adding urea to the first solvent, ultrasonicating for 15 minutes to make it dispersed evenly, obtaining a mixed solution, and freeze-drying the mixed solution to obtain a precursor, wherein the first solvent is deionized water. The ratio of the amount of urea to the volume of the first solvent is 50:10, the unit of the amount of the substance is mmol, and the unit of the volume is mL.
[0049] 2) The precursor was ground in a quartz mortar, and after grinding, the temperature was raised to 800° C. at a rate of 5° C. / min in an argon gas atmosphere and calcined at 800° C. for 2 h to obtain a carbon nanocatalyst.
[0050] Comparative Example 2
[0051] A method for preparing a carbon nanocatalyst (code: BNC) comprises the following steps:
[0052] 1) Urea and a B source are added to a first solvent, and ultrasonicated for 15 minutes to disperse them uniformly to obtain a mixed solution, and the mixed solution is freeze-dried to obtain a precursor, wherein the B source is boric acid, the first solvent is deionized water, and the ratio of B in urea and the B source is 50:3.2 in terms of molar fractions. The ratio of the molar fraction of urea to the volume fraction of the first solvent is 50:10, the unit of the molar fraction is mmol, and the unit of the volume fraction is mL.
[0053] 2) The precursor was ground in a quartz mortar, and after grinding, the temperature was raised to 800° C. at a rate of 5° C. / min in an argon gas atmosphere and calcined at 800° C. for 2 h to obtain a boron-nitrogen-doped carbon nanocatalyst.
[0054] Comparative Example 3
[0055] A method for preparing a carbon nanocatalyst (numbered as FeCN) is basically the same as that of Example 1, the only difference being that no B source is added in this preparation method.
[0056] Figure 1 The X-ray diffraction patterns of the carbon nanocatalysts prepared in Comparative Examples 1 to 3 and the B-doped iron single atom catalyst prepared in Example 1 are shown in FIG. Figure 1 It can be seen that the XRD spectra of the carbon nanocatalysts prepared in Comparative Examples 1 to 3 and the B-doped iron single atom catalyst prepared in Example 1 only identify two broad characteristic peaks, corresponding to the (002) and (101) crystal planes of the graphite carbon standard card, respectively.
[0057] Figure 2The transmission electron microscope (TEM) spectrum of the B-doped iron single-atom catalyst prepared in Example 1 is shown in FIG. Figure 2 It can be seen that the B-doped iron single-atom catalyst prepared in Example 1 presents a thin graphene structure without obvious iron nanoparticles and iron nanoclusters.
[0058] Figure 3 This is an energy dispersive X-ray spectroscopy (EDS) mapping diagram of the B-doped iron single-atom catalyst prepared in Example 1, where (a) is the C element, (b) is the N element, (c) is the B element, and (d) is the Fe element. Figure 3 Analysis shows that the C atoms, B atoms, N atoms and Fe atoms in the B-doped iron single atom catalyst prepared in Example 1 are evenly distributed. Figure 2 and Figure 3 , proving that iron atoms exist in the form of single atoms.
[0059] Figure 4 The Fourier transform extended X-ray absorption fine structure (FT-EXAFS) spectrum of the B-doped iron single atom catalyst prepared in Example 1, wherein: Figure 4 "Fe2%-BCN" is the test curve of B-doped iron single atom catalyst prepared in Example 1 by FT-EXAFS. Figure 4 "Fe-B" represents the coordination curve of Fe-B bond. Figure 4 "Fe-N" in the figure is the coordination curve of the Fe-N bond. Figure 4 The “Total fit” in the figure is the fitting result of the test curve of the B-doped iron single atom catalyst prepared in Example 1 (without the impurity peaks), Figure 4 It can be seen that the B-doped iron single atom catalyst prepared in Example 1 The bond length at is attributed to the Fe-N bond, and the coordination number of the Fe-N bond is 4.1. The bond length at is attributed to the Fe-B bond, and the coordination number of the Fe-B bond is 1.3. It can be further known that the coordination number ratio of the Fe-N bond to the Fe-B bond is about 4:1, which indicates that the first shell coordination structure of the Fe atom is Fe-N4 coordination with four N atoms and Fe coordination with a single B atom. Therefore, the B-doped iron single atom catalyst is the Fe-N4B1 atomic configuration. Figure 1 to Figure 4 , indicating that the B-doped iron single-atom catalyst prepared in Example 1 was successfully prepared.
[0060] Sulfamethoxazole (SMX) degradation experiment:
[0061] (1) Under normal pressure, a catalyst was added to a 100 mL beaker containing 50 mL of a sulfamethoxazole solution to make the catalyst concentration 0.2 g / L, and magnetic stirring was performed for 30 min to reach adsorption-desorption equilibrium to obtain a suspension, wherein the pH of the suspension was 7.0, the catalyst was one of the B-doped iron single atom catalysts prepared in Examples 1 to 8 and the carbon nanocatalysts prepared in Comparative Examples 1 to 3, and the concentration of sulfamethoxazole in the sulfamethoxazole solution was 10 mg / L (C0).
[0062] (2) PMS is added to the above suspension to make the concentration of PMS in the suspension 0.2 g / L to obtain a sample solution. Stirring is continued, and 2 mL of the sample solution is taken at the T min of stirring and filtered with a 0.22 μm filter membrane. After filtration, the concentration (C) of sulfamethoxazole in the sample solution is determined by high performance liquid chromatography, wherein T min is 1 min, 3 min, 5 min, 10 min and 15 min, respectively.
[0063] Figure 5 The effect diagram of sulfamethoxazole degradation is shown in Figure 1. The catalyst in (a) is one of the B-doped iron single-atom catalysts prepared in Examples 1 to 8, and the catalyst in (b) is one of the B-doped iron single-atom catalysts prepared in Example 1 and the carbon nanocatalysts prepared in Comparative Examples 1 to 3. Figure 5 It can be seen from (a) that the B-doped iron single-atom catalysts prepared in Example 1, Examples 3 to 5 and Example 7 all have excellent degradation effects on sulfamethoxazole. Among them, the B-doped iron single-atom catalyst prepared in Example 1 has the best degradation efficiency for sulfamethoxazole, achieving 100% degradation of sulfamethoxazole within 5 minutes, which is higher than the B-doped iron single-atom catalysts with other Fe ratios and B ratios. Figure 5 As can be seen from (b), the degradation effect of the B-doped iron single-atom catalyst prepared in Example 1 on sulfamethoxazole is much higher than that of the carbon nanocatalysts prepared in Comparative Examples 1 to 3.
[0064] In order to better understand the mechanism of the degradation and conversion process, the main active species (·OH, SO4 2- 、O2 - and 1 O2), set up the following experimental groups:
[0065] PMS group: PMS and a capture agent were added to 3 mL of the third solvent (the third solvent was ultrapure water or methanol) to obtain a test solution, wherein the initial concentration of PMS in the test solution was 0.2 g / L.
[0066] FeBCN group: Add the catalyst and the capture agent to 3 mL of the third solvent (the third solvent is ultrapure water or methanol) to obtain a test solution, wherein the initial concentration of the catalyst in the test solution is 0.2 g / L, and the catalyst is the B-doped iron single-atom catalyst prepared in Example 1.
[0067] FeCN+PMS group: PMS, a catalyst and a capture agent were added to 3 mL of the third solvent (the third solvent was ultrapure water or methanol) to obtain a test solution, wherein the initial concentration of PMS in the test solution was 0.2 g / L, the initial concentration of the catalyst in the test solution was 0.2 g / L, and the catalyst was the iron single atom catalyst prepared in Comparative Example 3.
[0068] FeBCN+PMS group: PMS, a catalyst and a capture agent were added to 3 mL of the third solvent (the third solvent was ultrapure water or methanol) to obtain a test solution, wherein the initial concentration of PMS in the test solution was 0.2 g / L, the initial concentration of the catalyst in the test solution was 0.2 g / L, and the catalyst was the B-doped iron single-atom catalyst prepared in Example 1.
[0069] The capture agent added to the PMS group, FeBCN group, FeCN+PMS group and FeCN+PMS group was 5,5-dimethylpyrroline N-oxide (DMPO) or 2,2,6,6-tetramethylpiperidinol (TMP), wherein the initial concentration of 5,5-dimethylpyrroline N-oxide (DMPO) in the test solution was 10uL / mL, and the initial concentration of 2,2,6,6-tetramethylpiperidinol (TMP) in the test solution was 10uL / mL.
[0070] The test solutions of the PMS group, FeBCN group, FeCN+PMS group, and FeBCN+PMS group were shaken for 5 min, and all the test solutions were aspirated with capillaries. EPR spectra were measured at room temperature using a Bruker A300 spectrometer. Hydroxyl radicals (·OH) and sulfate radicals (SO4 2- ), capturing superoxide radicals (·O 2- ), 2,2,6,6-tetramethylpiperidinol (TMP) capture agent captures singlet oxygen in an ultrapure water system (the third solvent is ultrapure water) 1 O2) to detect the active species generated by the B-doped iron single atom catalyst prepared in Example 1. The test results are as follows Figure 6 As shown by Figure 6 As shown in (a), since the strength of the signal peak of the active species represents its response intensity, there is no ·OH and SO4 in the FeBCN+PMS group. 2-, Figure 6 From (b) and (c), we can see that the FeBCN+PMS group has ·O 2- and 1 O2. Further 2- as well as 1 The signal peak intensity of O2 is compared with Figure 7 It can be seen that 1 O2, O 2- The signal peak of the same vertical coordinate response range is relative to 1 O2, O 2- The signal peak intensity of can be ignored, so it is concluded that the main reactive oxygen species in the FeBCN+PMS group are 1 O2.
[0071] In order to further explore the degradation products, the sample solution of the B-doped iron single atom catalyst prepared in Example 1 of the "Sulfamethoxazole (SMX) Degradation Experiment" as a "catalyst" to degrade sulfamethoxazole was subjected to liquid mass analysis at 0 min, 2 min, 4 min, 6 min and 10 min of stirring. The specific operation is as follows: the sample solution is loaded onto a BEH C18 column, and the sample solution is separated at a flow rate of 0.20 mL / min using a gradient of the volume ratio of mobile phase A and mobile phase B from (95:5) to (5:95), wherein the mobile phase A is a mixture of formic acid and water, the content of formic acid in solvent A is 0.1% (v / v), the mobile phase B is acetonitrile, and the column temperature is 40°C. The accurate tandem mass spectrometry (MS / MS) spectra of sulfamethoxazole (SMX) and its degradation products are analyzed using positive electrospray ionization mode (mass-to-charge ratio (m / z): 20-1000). The molecular formula of the product was identified based on the experimental and theoretical m / z values, and the possible products were summarized and analyzed. The results are as follows Figure 8 As shown by Figure 8 It can be seen that SMX 1 The chemical bonds were broken step by step by the continuous oxidation and mineralization of O2. At the 4th minute of degradation, the generation of substances with relatively low molecular weight was monitored. At the 10th minute of degradation, the final 1 Under the oxidation of O2, SMX is completely mineralized into carbon dioxide and water.
[0072] Microplastic degradation experiment: Add the catalyst, PMS and microplastics to 100 mL of ultrapure water to obtain a test solution, and stir magnetically for 24 hours. The catalyst is the B-doped iron single-atom catalyst prepared in Example 1, and the initial concentration of the catalyst in the test solution is 0.2 g / L. The initial concentration of PMS in the test solution is 0.2 g / L, and it is added every two hours. The microplastic is polyvinyl chloride (PVC) or polylactic acid (PLA), and the initial concentration of PVC in the test solution is 7 g / L, and the initial concentration of PLA in the test solution is 7 g / L.
[0073] After stirring for 24 h, 2 μL of the test solution was injected into the gas chromatograph injector (the temperature of the gas chromatograph injector was set to 250° C.), and the product in the test solution was analyzed on an HP 6890-Plus gas chromatograph-mass spectrometer to obtain a gas chromatographic (GC) mass spectrum. The results are as follows: Fig. 9 As shown in the figure, about 15 peaks appeared in the gas chromatography mass spectra of the test liquid with PVC or PLA added to the microplastics, corresponding to the products after their respective transformations. In order to understand the composition of the products in detail, the NIST database was used for product screening and the possible carbon products were summarized. It can be seen that the products are mainly concentrated in C 10 -C 20 , among which 2-heptyl-1,3-dioxolane (2-heptyl-1,3-Dioxolane, molecular formula: C 10 H 20 O2) is the majority, about 14%, 2-heptyl-1,3-dioxolane (2-heptyl-1,3-Dioxolane) is mainly used as a solvent for oil and fat, an extractant, an electrolytic solvent for lithium batteries, a chlorine-based solvent stabilizer and a pharmaceutical intermediate. 2-Heptyl-1,3-dioxolane is also the second monomer of copolymer formaldehyde, and is copolymerized with trioxymethylene at a ratio of 95:5 to produce copolymer formaldehyde, which can be used as a solvent, a silk finishing agent and a sealing glue. Therefore, the B-doped iron single-atom catalyst prepared in Example 1 has a good degradation ability for microplastics, and its product can be utilized as a resource.
[0074] The present invention is described above by way of example. It should be noted that, without departing from the core of the present invention, any simple deformation, modification or other equivalent replacement that can be made by those skilled in the art without inventive effort falls within the protection scope of the present invention.
Claims
1. A method for preparing a B-doped iron single-atom catalyst, characterized in that: The following steps are involved: 1) Dispersing urea and B source uniformly in a first solvent to obtain a mixed solution, uniformly mixing an Fe source solution, a polyether F127 solution and the mixed solution, and freeze-drying to obtain a precursor, wherein the Fe source solution is a mixture of the Fe source and the second solvent, the polyether F127 solution is a mixture of the polyether F127 and the second solvent, and the ratio of urea to B in the B source and Fe in the Fe source is 50: (2.5-5.5): (0.02-0.08) in terms of the amount of the substance; 2) calcining the precursor at 780-820° C. for 1.8-2.2 h in a nitrogen or inert gas atmosphere to obtain a B-doped iron single atom catalyst.
2. The preparation method according to claim 1, characterized in that: The ratio of the amount of Fe in the Fe source to the mass of the polyether F127 is (0.02-0.08):200, the unit of the amount of Fe is mmol, and the unit of the mass is mg.
3. The preparation method according to claim 1, characterized in that: The concentration of Fe element in the Fe source solution is 3.5-4.5 mmol / L, and the concentration of polyether F127 in the polyether F127 solution is 35-45 mg / mL.
4. The preparation method according to claim 1, characterized in that: The ratio of the amount of urea to the volume of the first solvent is 50:(9-11), the unit of the amount of urea is mmol, and the unit of the volume is mL.
5. The preparation method according to claim 1, characterized in that: The B source is boric acid, the Fe source is ferric chloride hexahydrate, the first solvent is deionized water, and the second solvent is ethanol.
6. The preparation method according to claim 1, characterized in that: The heating rate of the calcination is 4.5-5°C / min, and the precursor needs to be ground before calcination.
7. Use of the B-doped iron single-atom catalyst obtained by the preparation method as described in any one of claims 1 to 6 in the degradation of microplastics or pollutants.
8. The use according to claim 7, characterized in that: The pollutant is sulfamethoxazole, and the microplastic is polyvinyl chloride or polylactic acid.
9. The use according to claim 7, characterized in that: The reaction for degrading microplastics or pollutants is a Fenton-like degradation that requires the addition of potassium permonosulfate complex salt. The conditions for degrading microplastics are normal pressure, and the pH for degrading microplastics or pollutants is 6.0-8.
0.
10. A B-doped iron single atom catalyst comprising: The carrier and the B element and iron element doped in the carrier, the B-doped iron single-atom catalyst is a Fe-N4B1 atomic configuration, the iron element exists in the form of a single atom, the carrier is g-C3N4, and the C atoms, B atoms, N atoms and Fe atoms are evenly distributed in the B-doped iron single-atom catalyst.
Citation Information
Cited By
A method for stably and efficiently degrading organic wastewater by using a non-metallic single-atom carbon-nitrogen catalyst
CN122748804A